Platelet Rich Fibrin Matrix (PRFM) and Peripheral Blood Mesenchymal Stem Cells (PBMSCs) in the management of intraosseous defects - A randomized clinical trial - R SREEPARVATHY; Sphoorthi Anup BELLUDI; Ashwin PRABHU (University of São Paulo, 2024)
Abstract A combination of peripheral blood mesenchymal stem cells (PBMSCs) and platelet rich fibrin matrix (PRFM) could be a probable periodontal regenerative material with the synergy of the added benefits of each material. Objective This randomized controlled clinical trial aimed to evaluate the regenerative capacity of supercell (PRFM and PBMSCs) compared with that of PRFM alone in human periodontal mandibular intraosseous defects (IOD). Methodology This study included 17 patients of both sexes (12 men, 5 women) aged 30-55 years (mean age = 37.7±4.4 years) who fulfilled the inclusion criteria (radiographic and clinical evaluation for bilateral IOD with probing pocket depth (PPD ≥ 6 mm). A split-mouth design was used in each patient. A total of 34 sites in the mandibular arch randomly received PRFM alone + open flap debridement (OFD) [Control sites] or supercell (PRFM+PBMSCs) + OFD [Test sites]. The clinical parameters plaque index (PI), gingival index (GI), PPD, clinical attachment level (CAL), and in the radiographic parameters; defect depth (DD) and defect fill percentage (DFP) were recorded at baseline, 3 and 6 months postoperatively. Early wound healing index (EHI) was used at 1 week to assess wound healing ability. Results At 6 months, radiographic parameters revealed significant reduction in DD (P<0.001) and significant DFP values in the test group compared with the control group. The supercell showed significant improvement in PPD and CAL at the end of 6 months (P<0.001). EHI scores at 1 week showed no statistically significant difference between the test and control groups. Conclusion Supercell can be considered a regenerative material in the treatment of periodontal IODs.